SISTEM INFORMASI AKUNTANSI PENGENDALIAN INTERN TERHADAP PERSEDIAAN BAHAN BAKU (Studi Kasus Pada PT. Geomed Indonesia) - Fatmawati, Rizky Laelatul; Sulistyawati, Ardiani Ika (Fakultas Ekonomi, Universitas Semarang, 2021)
This study was conducted in PT. Geomed Indonesia. The purpose of this study are : (1) To find out the method of recording raw material inventory system at PT. Geomed Indonesia, (2) To find out the procedures that make up the raw material inventory system at PT. Geomed Indonesia, (3) To find out the elements of internal control contained in the accounting system for raw material inventories at PT. Geomed Indonesia, (4) To find out whether the internal control accounting information system for raw material inventories is effective enough for the company. The method of research analysis used is desccriptive qualitative method, with research data sources using primary data and secondary data obtained through interview techniques, observation and literature review. The basoc of the informant principle in this study is 3 people.From the results of study indicate that the internal control accounting information system carried out is quite good because there already is a task separator, manual and computerized recording and supervision of the leadership. However, it is necessary to add the Receiving function within the company to ensure that internal control accounting information system is carried out properly.Keyword : Accounting System, Inventory, Raw Materials